Development of new isolates of shiitake mushroom through hyphal anastomosis of single spore cultures - S.S. SHARMA, R.K. SAMOTA* and (Indian Phytopathology, 2008)
Four parents were used to develop new isolates of shiitake mushroom through mycelial anastomosis. Total six combinations were made through dual culture technique. Out of these maximum frequency of anastomosis (80-100%) was observed in four combinations like Le 4/03 × Le 7/04, Le 4/03 × LeOE 9, LeOE 9 × LeOE 142 and LeOE 9 × Le 7/04 and remaining two were below 80 per cent. Mycelial growth of most of the parent strains and new isolates were fluffy white with circular colony growth and zonation at periphery except LeOE 142, LeOE 9 × LeOE 142 and LeOE 142 × Le 7/04 where appressed milky mycelial appearances with circular growth, faintly zonate and uneven margins were found. Pigmentation was positive in all the strains and isolates. The isolate LeOE 142 × Le 7/04 took 49 days to complete spawn run which is highest in all the strains and isolates tried but rest of the five new isolates were found to complete early spawn run. Over all, average time taken in fruit body harvest from the day of spawning was found less in newly developed isolates over the parent strains. In yield trials, three isolates viz. LeOE 9 × Le 7/04, LeOE 9 × LeOE 142 and Le 4/03 × LeOE 9 recorded 25 per cent increase yield. Remaining new isolates yielded below average of the parent strains. Number of fruit bodies was not affected but there was increase in individual fruit body weight.